Bioequivalence evaluation of two amlodipine salts, besylate and orotate, each in a fixed-dose combination with olmesartan in healthy subjects - Lee, Soo-Yun (Drug Des Devel Ther, 2015)
A fixed-dose combination of amlodipine and olmesartan is used to treat high blood pressure in patients whose hypertension is not sufficiently controlled with either drug alone. The objective of this study was to evaluate the bioequivalence of two fixed-dose combinations, ie, amlodipine orotate/olmesartan medoxomil 10/40 mg and amlodipine besylate/olmesartan medoxomil 10/40 mg, in healthy subjects. A randomized, open-label, single-dose, two-sequence, two-period, crossover study was conducted in 30 healthy adult volunteers. Blood samples were collected for up to 72 hours post-dose in each period. Safety data included the results of physical examinations, clinical laboratory tests, vital signs, an electrocardiogram, and adverse events. For both amlodipine and olmesartan, the 90% confidence intervals for the geometric mean ratios of AUC(last) and time to peak plasma concentration fell within the bioequivalence acceptance criteria. The two fixed-dose combinations showed similar safety profiles. Amlodipine orotate/olmesartan medoxomil 10/40 mg was bioequivalent to amlodipine besylate/olmesartan medoxomil 10/40 mg.